2004
DOI: 10.1111/j.1440-1754.2004.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in neonates: Analysis of 14 Japanese patients

Abstract: Hypoxic events may play a crucial aetiologic role in the pathogenesis of late-onset neonatal intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 11 publications
1
26
0
4
Order By: Relevance
“…However, a lead point may be found in about 8% cases. In the present case, we did not find any lead point, similar to Anand et al 9 Ueki et al 10 in a recent study of 14 neonates concludes that hypoxic events may play a crucial aetiologic role in the pathogenesis of late onset neonatal intussusception.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, a lead point may be found in about 8% cases. In the present case, we did not find any lead point, similar to Anand et al 9 Ueki et al 10 in a recent study of 14 neonates concludes that hypoxic events may play a crucial aetiologic role in the pathogenesis of late onset neonatal intussusception.…”
Section: Discussionsupporting
confidence: 90%
“…Typical features are absent and the symptoms mimic other common surgical conditions 7. Mass is also infrequently palpated as against infantile intussusception 3 810…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the cardinal infantile symptoms of paroxysmal abdominal cramps, palpable mass, and currant jelly stools are often absent in the neonate. Instead, intussusception in the younger infant may present with nonspecific signs including abdominal distension, bilious emesis, and intolerance to feeding; rectal bleeding may also occur, mimicking NEC [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 95%
“…Inspissated meconium has also been found to be causing intussusception [14]. It has been observed that hypoxic events may play a crucial etiologic role in the pathogenesis of late onset neonatal intussusception [16].…”
Section: Review Articlementioning
confidence: 99%
“…It has numerous advantages like absence of harmful radiation exposure to the neonate, lead point identification and ability to diagnose ileo-ileal and other small bowel intussusceptions [1,15,16,19,24,30]. Sometimes, in neonates, the sigmoid colon lies in the right side along with distended small bowel loops, overlapping the intussusception [31].…”
Section: Review Articlementioning
confidence: 99%